PHARMACOECONOMIC ASPECT OF OMALIZUMAB APPLICATION AMONG THE PATIENTS, SUFFERING FROM THE BRONCHIAL ASTHMA - A.S. Kolbin; N.N. Klimko; B.V. Andreev (Union of pediatricians of Russia, 2008)
In the given article, the authors discuss the most difficult issue of the pediatrics, which is the treatment of the severe bronchial asthma. Our columnist is professor A.S. Kolbin introduces omalizumab, a new medication from the monoclonal antibodies group, to our readers. It allows practitioners to control the severe persistent bronchial asthma. The article accentuates the clinical effectiveness and pharmacoeconomic aspects of the medication application.Key words: bronchial asthma, severe run, treatment, monoclonal antibodies, children.